(untitled) (Research, Society and Development, 2022)
The speech therapist in Primary Health Care (PHC) is one of the professionals who can be part of the of the Family Health Support Center (FHSC). Among the health promotion and prevention actions, the professional can also provide group or individual assistance. The main demands for speech therapy in PHC are related to the development of children’s language, and it is known that the act of playing becomes a huge part in the process of learning and language stimulation. The present article has the main goal to report the experience of elaborating an informational material about the stimulation of children’s language development through play. The material was created at Taguatinga’s Basic Health Unit 1, Distrito Federal, and was delivered to families during speech therapy sessions. The material was well received by families, and also by other professionals. In addition, it proved to be an effective intervention material according to proposed ideas and also as a way of complementing the given orientations during speech-language appointment.